2012
DOI: 10.1039/c2dt12238c
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous asymmetric crystallization of a quartz-type framework from achiral precursors

Abstract: An enantioenriched three-dimensional quartz-type framework {[Ni(1.5)(tzdc)(H(2)O)(3)]·3H(2)O}(n) (H(3)tzdc = 4H-1,2,4-triazole-3,5-dicarboxylic acid) possessing chiral channels is obtained through spontaneous asymmetric crystallization without any enantiopure additive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Chiral surfaces and nanofilms with spatial fibrous morphology can be prepared using 3D templating systems, such as fibers and helical tubes. Chiral templated-surfaces can be fabricated using different chemical processes, among are sol–gel approach, atomic layer deposition (ALD), and chemical vapor deposition (CVD) . For example, chiral-templated single-handed helical zirconia nanotubes and chiral titania fibers were prepared by the sol–gel approach.…”
mentioning
confidence: 99%
“…Chiral surfaces and nanofilms with spatial fibrous morphology can be prepared using 3D templating systems, such as fibers and helical tubes. Chiral templated-surfaces can be fabricated using different chemical processes, among are sol–gel approach, atomic layer deposition (ALD), and chemical vapor deposition (CVD) . For example, chiral-templated single-handed helical zirconia nanotubes and chiral titania fibers were prepared by the sol–gel approach.…”
mentioning
confidence: 99%
“…The Flack parameter finds widespread use in the study of novel chiral systems such as helicates, cyclic helicates and knotted systems exhibiting topological chirality and has been used to establish the absolute configuration of molecular trefoil knots assembled in self-sorting processes [152]. The use of the Flack parameter to establish the asymmetric crystallization of coordination networks and metal-organic frameworks is an interesting new development [153][154][155].…”
Section: The Influence Of Flackmentioning
confidence: 99%
“…Generally, CCPs could be obtained by introducing certain chiral agents to play as components, counterions, templates, or structural directing agents. The limited species of commercial chiral agents and their high cost have hindered the development of CCPs. On the other hand, people have found that CCPs could also be prepared by adopting normal achiral starting materials, without any chiral agents (named a CCPs in the following discussion). This phenomenon is usually called “spontaneous resolution”. However, the products of those a CCPs were always racemic mixture (conglomerates) or racemic solid solution, which makes the study of application difficult.…”
Section: Introductionmentioning
confidence: 99%